Polymer-Surfactant Complex for Enhancing the Mechanical and Drag Reduction Performances of a Turbulent Flow - Abdulbari, Hayder A.; Hawege, Emsalem (AENSI Publishing, 2015)
Polymer additives in drag reduction (DR) are vulnerable to the mechanical and the thermal degradation. In the present work, an interaction between nonionic polymer Hydroxypropyl cellulose and anionic surfactant sodium Oleate (HPC -S.O) complex in aqueous solution has been studied by using rheology and RDA techniques to evidence complex capability and stability in enhancing the drag reduction and mechanism degradation performance, respectively. The effect of the concentration of the polymer on the drag reduction and the effect of increasing concentration of surfactant to the polymer-surfactant complex in enhancing the drag reduction were studied. In addition, the effect of the rotational speed on the drag reduction has also been studied. A maximum of 48 % DR was observed at 500 rpm with a concentration of 1000 ppm of HPC-S.O complex.